(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
The paper provides an overview of the Croatian translation of IFLA documents, guidelines, manuals and standards published by the Croatian Library Association (CLA), including both documents as standalone editions in monographs and parts of proceedings or serial publications. For this purpose we have made the bibliography of translations including the year 2014. Data on the published translations have been analyzed according to quantitative and qualitative parameters. Based on the collected data, the author has tried to determine if there is a need for further publication of translations of IFLA’s documents in the edition of CLA. The paper provides an insight into the issue of publishing by professional associations in Croatia.